Alfresco One 5.x developer's guide : discover what it means to be an expert developer by exploring the latest features available to you in Alfresco One 5.x - Chevallereau, Benjamin; Potts, Jeff (Packt Publishing, 2017)
Discover what it means to be an expert developer by exploring the latest features available to you in Alfresco One 5.x About This Book Create reliable and secure enterprise apps with the latest Alfresco One 5.x platform Explore all the latest Alfresco One 5.x APIs such as the CMIS API, Alfresco One API, and the integrated RESTful API to get more out of your enterprise apps Unleash the power of the latest JavaScript engine and the JavaScript API for Alfresco to customize your existing apps for the Alfresco 5 platform Who This Book Is For If you're an enterprise app developer who wants to create custom applications with Alfresco, then this book is for you. Previous knowledge with Alfresco would be helpful but is not necessary. What You Will Learn Create and manage a custom content model Configure the Alfresco Share user interface Build a new AngularJS 2.0 application Create business process definitions using Activiti Designer Discover the most common extensions provided by Alfresco Configure Alfresco to authenticate against LDAP, including & chaining" LDAP with Alfresco authentication Get familiar with the latest features of Alfresco Mobile SDK, Smart Search, and the new Angular framework In Detail Do you want to create more reliable and secure solutions for enterprise apps? Alfresco One 5.x is your gateway to developing the best industry-standard enterprise apps and this book will help you to become a pro with Alfresco One 5.x development. This book will help you create a complete fully featured app for your organization and while you create that perfect app, you will explore and implement the new and intriguing features of Alfresco. The book starts with an introduction to the Alfresco platform and you'll see how to configure and customize it. You will learn how to work with the content in a content management system and how you can extend it to your own use case. Next, you will find out how to work with Alfresco Share, an all-purpose user interface for general document management, and customize it. Moving on, you write web scripts that create, read, and delete data in the back-end repository. Further on from that, you'll work with a set of tools that Alfresco provides; to generate a basic AnglularJS application supporting use cases, to name a few authentication, document list, document view. Finally, you'll learn how to develop your own Alfresco Mobile app and understand how Smart Folders and Search manager work. By the end of the book, you'll...